2021
DOI: 10.1177/10398562211037339
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functioning and clinical outcomes in inpatient with schizophrenia on clozapine augmented with antipsychotics

Abstract: Objective: We aimed at exploring predictors of improvement in clinical and functional outcomes of patients on clozapine with chronic treatment-resistant schizophrenia admitted into rehabilitation wards. Method In a cross-sectional study of 62 patients on clozapine augmented with oral and parenteral antipsychotics, predictors of HoNOS (Health of the Nation Outcome Scales) scores were analysed using ordinal logistic regression. Result: Augmentation with parenteral antipsychotics was associated with lower psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Duration of follow up varied from 3 months 14 to 3 years 21 and it was not reported in three study 16,19,24 and not applicable in one study 18 …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Duration of follow up varied from 3 months 14 to 3 years 21 and it was not reported in three study 16,19,24 and not applicable in one study 18 …”
Section: Resultsmentioning
confidence: 98%
“…We retrieved a total of 12 relevant articles which included two case reports, three case series and seven retrospective observational studies, four of which followed a mirrorimage design, representing a total of 195 patients (Table 1). Three studies were conducted in Turkey, 14,15 two in South Korea 16,17 two in Australia 18,19 and one in each of the following countries: Spain, 20 Canada, 21 Italy, 22 France 23 and the United States. 24 Both first-generation and second-generation antipsychotics were reported as adjunctive treatment to clozapine, although second-generation appeared more frequently.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of symptoms, at the time of the first antipsychotic prescription in the observation window, was assessed using two items from the Health of the Nation Outcome Scale (HoNOS): (i) problems associated with hallucinations and delusions and (ii) problems with activities of daily living ( Mukherjee and Sazhin, 2022 ; Wing et al., 1998 ). Given the multiple assessments, we used a hierarchy: first, we retrieved the HoNOS scores in the 3 months before the first antipsychotic prescription; if none were available, we searched for information in the 3 months after the first antipsychotic prescription; if this was also unavailable, we retrieved the most recent HoNOS scores before the first antipsychotic prescription.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Although the literature on the effect of clozapine augmentation on functional outcomes as opposed to the management of positive symptoms is even less available, a recent cross-sectional study comparing parenteral and oral augmentation with clozapine showed an improvement in functioning as determined by one HoNOS (Health of the Nation Outcome Scales) item in the parenteral arm. 4 Given that positive symptoms as well as anxiety, negative, and cognitive symptoms have been shown to impact functional outcomes, [5][6][7] this study addressed the association of antipsychotics prescribed routinely to reduce positive symptoms in addition to clozapine on functioning measures collected in clinical practice.…”
mentioning
confidence: 99%